2020
DOI: 10.1002/lary.29196
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Tumor‐Infiltrating Lymphocytes in Laryngeal Squamous Cell Carcinoma Patients

Abstract: Objectives/Hypothesis: Tumor-infiltrating lymphocytes (TILs) has been shown to be associated with the prognosis of many tumors, yet few studies have investigated their roles in laryngeal squamous cell carcinoma (LSCC). We aim to investigate the prognostic values of tumor-infiltrating CD3 + /CD4 + /CD8 + /Foxp3 + T-cells and neutrophils in LSCC patients that received total or partial laryngectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…Of these, seven were excluded because they did not report the outcome of LSCC separately from other locations of HNSCC [ 12 , 15 , 16 , 17 , 18 , 19 , 20 ], eight because no HRs were available [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], one study because they reported outcome in terms of local control [ 30 ], one study that evaluated Il-12R expression on tumor cells [ 31 ], and one study that evaluated lymphocytes in peripheral blood [ 32 ]. This left 11 studies for the analysis ( Figure 1 ) [ 9 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. All the studies included in this review were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, seven were excluded because they did not report the outcome of LSCC separately from other locations of HNSCC [ 12 , 15 , 16 , 17 , 18 , 19 , 20 ], eight because no HRs were available [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], one study because they reported outcome in terms of local control [ 30 ], one study that evaluated Il-12R expression on tumor cells [ 31 ], and one study that evaluated lymphocytes in peripheral blood [ 32 ]. This left 11 studies for the analysis ( Figure 1 ) [ 9 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. All the studies included in this review were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies showed a survival advantage for the cases with high CD8+ TIL. The pooled meta-analysis showed an ad- The prognostic value of CD8+ TIL was assessed in six eligible studies for inclusion in the meta-analysis [9,35,[37][38][39]41] (Figure 3). All the included studies showed a survival advantage for the cases with high CD8+ TIL.…”
Section: References Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations